Pengaruh Modal Minimum, Pemahaman Investasi, Return. Risiko dan Motivasi Terhadap Minat Mahasiswa Berinvestasi di Pasar Modal Syariah - Annisa, Sufiati; Soemitra, Andri; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2023)
Investment is an important factor in increasing economic growth and development in a country. Young people can play an important role in driving this outcome by participating in government projects designed to attract new investors to the country, especially students. This study aims to analyze the effect of minimum capital, investment knowledge, return, risk and motivation on students interest in investing in Medan. The subjects of this study were active S1 students of the Faculty of Economics and Economics, University of Medan who already owned the Indonesia Stock Exchange Investment Gallery with a total of 25,767 students. This study used convenience sampling, namely respondents were selected because they were suitable for researchers. By collecting sample of 100 people. The data analysis technique used are descriptive analysis and multiple regression analysis to describe the relationship between the independent variables and the dependent variable. The results of this study indicate that the effect of minimum capital, investment understanding, return, risk, and motivation has a significant positive effect on students investment intentions in the city of Medan. Based on the Adjust R2 results of 57.2 For further research, it is suggested to use variables other than those used in this study or add additional variables.